Meningkatkan pengetahuan orang tua dalam mendidik anak di era digital di Kecamatan Koto Gasib Kabupaten Siak Provinsi Riau - Ria Novianti; Febrialismanto Febrialismanto; Enda Puspitasari; Hukmi Hukmi (Riau Journal of Empowerment, 2020)
This community service activity aims to improve the knowledge of parents in educating children in the digital era. It is important to be done so that parents can respond to technological developments and adjust parenting for children, so technology which is essentially created for the ease and goodness of human life, will not give negative affect children and adolescents. Therefore, parents need to have adequate information and knowledge. Through this activity, we convey a variety of materials on how to educate children in the digital age with the hope that young children will be able to socialize, empathize, speak well, and be healthy, both physically and spiritually. The activities are divided into two parts, socialization, and training, while the participants of this activity are mothers in Koto Gasib District Siak Regency, which has young children. From the implementation of this community service, it can be concluded. There was an improvement in parent’s knowledge. Pretest results were 47.61% and increased to 76.90% on posttest. This indicates that the community service activity went well and effectively.